Sono e aprendizagem em Octopus insularis - Paiva, Mizziara Marlen Matias de (2023)
Among invertebrate animals, the class of cephalopods has stood out in research for its remarkable intelligence and learning ability. In particular, octopuses have shown complex behavior regarding the organization of their nervous system, which includes a lobe for learning. These animals also show, as already known in vertebrates, learning skills by touch and observation. In the literature, there are studies carried out with the species O. vulgaris in which it was verified that octopuses are able to change behavior based on the results of experiments, demonstrating that they can associate information and reproduce adaptive behavioral responses. Sleep is a behavior that occurs in several taxa of the animal kingdom and has already been extensively studied in vertebrates, especially in mammals and birds. However, among invertebrates, in the case of octopuses, there are behavioral and electrophysiological studies that point to the existence of at least two sleep phases. Among the objectives of this study, we seek to relate the learning capacity of these animals with the quiet and active sleep patterns, as well as to investigate and describe in detail, through a comprehensive behavioral quantification, a learning process in the species Octopus insularis. In order to do that, we submitted the animals to a task called “Russian Dolls”. Using video recordings, we are assessing whether the young adults of this species are capable of learning a new task, which requires the animals to sequentially open up to three different jars, one inside the other, one smaller than the other, with a reward (crab or shrimp) inside the smaller jar. We observed that the octopuses are able to open the 3 types of jars, often opening each of them in many different ways, which shows the cognitive ability and behavioral versatility of these animals, showing a significant value to the bigger jar step. Regarding the sleep monitoring, it was observed that the learning task caused changes in the duration of the active sleep episodes before and after the task.